Pronominalkasus i subjekt med bestemmende relativsætning - Petersen, Jan Heegård; Schack, Jørgen; Jensen, Eva Skafte (Ny forskning i grammatik, 2020)
This paper reports a study of the distribution of the nominative and the oblique form in personal pronouns in Danish, specifically the distribution of the two case forms in subjects constructed as a personal pronoun with a restrictive relative clause (of the type de/ dem der kom til tiden, fik en god plads ‘they/them who arrived on time, had a good seat’). The distribution is studied in written as well as spoken data. The aims are 1) to map out the actual distribution in authentic data, 2) to explain any discrepancies from the norm, be it in terms of register (spoken vs. written data) and/or grammatically